Frame innovation : create new thinking by design - Dorst, Kees, ....- (Cambridge : The MIT Press, 2015)
When organizations apply old methods of problem-solving to new kinds of problems, they may accomplish only temporary fixes or some ineffectual tinkering around the edges. Today's problems are a new breed -- open, complex, dynamic, and networked -- and require a radically different response. In this book, Kees Dorst describes a new, innovation-centered approach to problem-solving in organizations: frame creation. It applies "design thinking," but it goes beyond the borrowed tricks and techniques that usually characterize that term. Frame creation focuses not on the generation of solutions but on the ability to create new approaches to the problem situation itself.
Includes bibliographical references and index.
Keywords: Verandermanagement; Industrial design -- Methodology; Innovatie ; ondernemingen